POLIKARPUS SEBAGAI TELADAN MATI SYAHID DALAM KONTEKS KEBEBASAN BERAGAMA - Zein Marshellin Rante; Delsiana Palayukan, Abraham Mayor, Lindayani (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This study aims to explore the story of Polycarp as a model of martyrdom and its relevance to religious freedom. The qualitative method of case studies is used with in-depth literature study techniques. The results show that the story of Polycarp represents the values of courage, loyalty, integrity, and sacrifice that are very relevant in contemporary religious freedom struggles. The similarity in the pattern of violations of religious freedom between the time of Polycarp and the modern era reminds us of the urgency to continue fighting for human rights. Polycarp's experience can also inspire and motivate religious minorities who are still struggling to obtain the right to religious freedom.